Terminal value calculation with discontinuous financing and debt categories - Stefan Dierkes; Imke de Maeyer (Journal of Business Economics, 2022)
Empirical analyses indicate that active and passive debt management have limited power to explain the financing behavior of firms. Therefore, discontinuous financing, as a combination of active and passive debt management, might be a more realistic financing strategy. However, the properties of this financing strategy for the steady state have not yet been sufficiently analyzed. For this reason, we investigate analytically terminal value calculation with discontinuous financing and derive adjustment formulas for the period-specific levered cost of equity. Since a single adjustment of the entire debt at the beginning of every planning phase might still not be close to the real financing behavior of firms, we modify discontinuous financing by introducing debt categories, which are adjusted successively and include the maturity of debt. For this new financing strategy, we derive valuation equations and an adjustment formula for the constant cost of equity. Finally, we discuss the relevance and applicability of discontinuous financing with debt categories and its impact on the market value of a firm.
Keywords: G12; G31; G32; 650; Valuation; Terminal value calculation; Financing strategy; Discontinuous financing; Debt categories; Steady state